'Genre Blurring' and Public Administration: What Can We Learn from Ethnography?1. Issue 3 (September 2014) - Rhodes, R. A. W.
<x xml:space="preserve">Abstract</x> This article seeks to broaden the craft of public administration by 'blurring genres'. First, I explain the phrase 'blurring genres'. Second, I provide some examples of early work in administrative ethnography. Third, I compare this early, modernist‐empiricist ethnography with interpretive ethnography, suggesting researchers confront three choices: naturalism vs. anti‐naturalism; intensive vs. hit‐and‐run fieldwork; and generalisation vs. local knowledge. After this general discussion, and fourth, I discuss the more prosaic issues that confront anyone seeking to use ethnography to study public administration and look at fieldwork roles, relevance, time, evidence and fieldwork relationships. Fifth, I describe and illustrate the several tools students of public administration can use as well as observation and interviews; namely, focus groups, para‐ethnography, visual ethnography, and storytelling. Finally, I conclude that ethnographic fieldwork provides texture, depth and nuance, and lets interviewees explain the meaning of their actions. It is an indispensable tool and a graphic example of how to enrich public administration by drawing on the theories and methods of the humanities.